PENERAPAN MODEL PEMBELAJARAN TWO STAY TWO STRAY DALAM MENINGKATKAN KREATIVITAS SISWA PADA MATERI BUMI DAN TATA SURYA - Jamratul Ula; Zulkarnaini Zulkarnaini; Syarifah Rahmiza Muzana; Rina Mirdayanti (Jurnal Dedikasi Pendidikan, 2024)
The research aims to enhance the creativity of students by applying the TSTS (Two Stay Two Stray) learning model at SMPN 2 Kuta Baro Aceh Besar. The sample in this study was a student of class VII C of 22 students. This research uses a pre-experimental research design. Creativity data is collected through the observation sheet with the Guttman scale. Analysis of data creativity is calculated using a percentage formula. The study results of the student's learning creativity at the initial observation were 54.5% being in the category quite creative and the final observation score was 82% with the category highly creative. It can be concluded that the application of the learning model of Two Stay Two Stray can enhance the creativity of students of grade VII C at SMPN 2 Kuta Baro on Earth and Solar System matter.